Resistance of primary isolates of human immunodeficiency virus type 1 to neutralization by soluble CD4 is not due to lower affinity with the viral envelope glycoprotein gp120. - Turner, S (1992)
Recombinant soluble CD4 (rsCD4) has potent antiviral activity against cell line-adapted isolates of the human immunodeficiency virus type 1 (HIV-1) but low activity toward HIV-1 primary isolates from patients. A simple hypothesis proposed to explain this discrepancy, which questions the therapeutic utility of soluble CD4-based approaches, is that the major envelope glycoprotein, gp120, of patient virus has lower affinity for CD4 than does gp120 from laboratory viruses. To test this hypothesis, we have produced pairs of low- and high-passage HIV-1 isolates which, depending on culture passage history, display dramatically different sensitivities to neutralization by rsCD4. Here, we present evidence that the HIV-1 major envelope glycoprotein cDNAs cloned from one such isolate pair show only minor differences in their deduced gp120 primary structures, and these occur outside regions previously shown to be involved in CD4 interactions. In addition, recombinant gp120 from a low-passage rsCD4-resistant patient virus binds rsCD4 with high affinity, equal to that previously measured for recombinant gp120 from high-passage cell line-adapted virus isolates. These data indicate that differences in CD4-gp120 affinity do not account for rsCD4 resistance in HIV-1 recently isolated from patients.